2008
DOI: 10.1186/1757-1626-1-314
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic carcinoid; a diagnostic dilemma: a case report

Abstract: Introduction: Primary hepatic carcinoid tumours (PHCTs) are extremely rare neuroendocrine neoplasms. Only 58 cases have been reported in the literature and less than 10 cases were functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
0
25
0
3
Order By: Relevance
“…However, the association of these tumors with non-NET markers such as AFP, CA-125 and CA-19-9 is not relevant. Finally, the PHNET can be diagnosed only after the extrahepatic primary sites are excluded (17). In recent research, CDX2 and TTF-1 were reported as markers of gastrointestinal and pulmonary NETs, respectively (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of these tumors with non-NET markers such as AFP, CA-125 and CA-19-9 is not relevant. Finally, the PHNET can be diagnosed only after the extrahepatic primary sites are excluded (17). In recent research, CDX2 and TTF-1 were reported as markers of gastrointestinal and pulmonary NETs, respectively (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…These methods may be considered for small tumors with diameters ≤3 cm because of direct damaging effect on the tumors (Huang et al, 2010). When a not well defined lesion is observed, a palliative cytoreductive surgery in combination with transcatheter arterial embolization (TACE) and subsequent administration of lanreotide (long acting somatostatin analogue) might be effective, as Touloumis et al showed recently (Touloumis et al, 2008). In our series, four patients with recurrence received monotherapy (chemotherapy or resection even conservative treatment) and all died; two patients with recurrence received combined-therapy and survived till now.…”
Section: Treatmentmentioning
confidence: 66%
“…There is still no report of effective systemic chemotherapy for PHNEC. transcatheter arterial chemoembo-lization (TACE), as the common treatment protocol for liver cancer, has an ideal effect for metastatic hepatic NEC according to a report, (Bloomston et al, 2007) For PHNEC, TACE has been reported to achieve good palliation in some unresectable patients (Touloumis et al, 2008), but there is no certain result with a large sample set. In some report, TACE is recommended for cases with unresectable and/or recurrence tumors, but the long-term survival is not usually good enough.…”
Section: Treatmentmentioning
confidence: 99%
“…For patients with unresectable disease, a non-surgical approach may be preferred. This involves the use of ablation, hepatic artery embolization and somatostatin analogues (10,11). Octreotide, a somatostatin analog may not only alleviate hormonal symptoms but may also have an anti-proliferative effect (12).…”
Section: Discussionmentioning
confidence: 99%